INFLUENCE OF ICT INTEGRATION ON STUDENTS' ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN AWKA SOUTH L.G.A OF ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated the influence of ICT integration on students’ academic performance in public secondary schools in Awka south local Government Area of Anambra State. Three research questions guided the study Descriptive survey research design was employed in the study. Population of the study comprised 2,096. Proportionate stratified random sampling technique was used to select 380 respondents from SS 2 student from 19 secondary schools in Awka South L.G.A of Anambra State. A 16- Item Questionnaire titled influence of ICT Integration on Students’ Academic Performance Questionnaire (IIISAPQ) developed by the researchers was the main instrument for data collection. The research instrument was validated by three experts two from the department of education Management and Policy and one from the department of educational Foundations, faculty of education, Nnamdi Azikiwe University Awka. Cronbach Alpha method which gave internal consistency reliability value 0.60, 061 and 0.65 for each of the three clusters and these score equally added up to yield an overall reliability value of 0.63 showing that the questionnaire was reliable for conducting the study. Data collated were analyzed using mean scores and standard deviation in order to answer research questions. The findings of the study indicated that the extent to which ICT integration influences students’ Academic performance were to a low extent. From the findings of this study, recommendations were proffered. And they include among others that secondary school administrators should organize conferences, seminars and workshop on ICT for teachers and students in order to promote both teaching and learning. However the government should provide ICT resources and digital tools for proper collaboration and communication among students, teachers and parents. Also Ministry of Education should integrate ICT into their curriculum to increase quality educational resources to enhance understanding and retention of complex concepts.
Keywords: ICT Integration, Students’ Academic Performance, Public Secondary Schools.